PELATIHAN PENANGANAN BAYI ASFIKSIA DI RSUD SYARIFAH AMBAMI RATU EBU BANGKALAN - Ulva Noviana; M. Hasinuddin (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2019)
Asphyxia Neonatorum is a condition in which the baby is unable to breathe spontaneously and regularly after birth. This is due to fetal hypoxia in the uterus and this hypoxia is associated with factors that arise in pregnancy, childbirth or sooner birth. Based on research from the World Health Organization (WHO), around the world there are 10,000,000 infant deaths, especially neonates per year (Katiandagho & Kusmiayi, 2015). The method used to carry out community service is to collect data on the competence of health workers in the Baby Room at Syarifah Ambami Ratu Ebu Bangkalan Hospital through interviews with the Head of the Room, several nurses and midwives and management to find out the needs of the Hospital. In addition, it is also necessary to observe the skill competence of nurses and midwives when caring for babies with asphyxia During the process of the training program, all health personnel who are scheduled to take part in the training can attend from the start of the activity to the end. During the training process, the participants were very enthusiastic and interactive in the discussion. Demonstration and simulation activities participants get the opportunity to practice